Energy consumption and quality of service in WBAN: A performance evaluation between cross-layer and IEEE802.15.4 (2017)
Different communication schemes for Wireless Body Area Networks (WBAN) pretend to achieve a fair tradeoff between efficient energy consumption and the accomplishment of performance metrics. Among those schemes are the Cross-layer protocols that constitute a good choice to achieve the aforementioned tradeoff by introducing novel protocol techniques which are away from the traditional communications model. In this work we assessed the performance of a WBAN cross-layer protocol stack by comparing it against the performance of the protocols of the IEEE802.15.4 standard, which is commonly used for WBAN deployment nowadays. We evaluated the performance of both, cross-layer and IEEE802.15.4 approaches, by means of a simulation, by using a popular network simulator and its frameworks for wireless networks. And then performed a statistical comparison and ascertained that the cross-layer protocol stack offers better performance regarding a tradeoff between efficient energy consumption and performance metrics in our particular test scenario. We observed that, in general, the cross-layer approach outperformed both modes of IEEE802.15.4 standard (slotted and unslotted) regarding energy consumption, end to end delay, packet loss rate and goodput. The results of our experiments reported that the cross-layer strategy saves up to 80% more energy than IEEE802.15.4 unslotted and it is only a 5% below the slotted mode. Regarding the quality of service metrics the performance was always better when using the cross-layer scheme.